Association of Air Pollution and Climatic Factors with Pneumonia in Children Under Five, Padang, West Sumatera: Ecological and Spatial Analysis - Yusra, Aldy; Alfian, Azyyati Ridha; Azmi, Fadilla; Novirsa, Randy (Jurnal Kesmas Jambi, 2026)
Pneumonia remains one of the leading causes of mortality among children under five in Indonesia. Air pollution and climatic factors may increase the risk of pneumonia in this vulnerable population. This study aimed to examine the associations between air pollution, climatic factors, and pneumonia incidence among children under five in Padang City during 2023–2024. An ecological study was conducted using secondary data collected within a 5-km radius of an Air Quality Monitoring Station (AQMS). Air Quality Index (AQI) data were obtained from the West Sumatra Environmental Agency, while daily pneumonia surveillance data were obtained from the Padang City Health Office. Data were analyzed using simple linear regression, multiple linear regression, and descriptive spatial analysis. In the adjusted multiple regression model, carbon monoxide (CO) (β = 0.00, p = 0.027) and ozone (O₃) (β = 0.28, p = 0.039) were positively associated with pneumonia incidence, with O₃ identified as the strongest predictor. In unadjusted analyses, each 1 µg/Nm³ increase in CO and O₃ concentrations was associated with increases of 0.01 and 0.43 daily pneumonia cases, respectively. Together, both pollutants explained 27% of the variation in pneumonia incidence (R² = 0.27). Spatial analysis showed that areas with higher CO and O₃ concentrations tended to have higher pneumonia incidence. Strengthening air pollution control and targeted public health interventions are essential to reduce the burden of childhood pneumonia.